Study the Effect Nanomaterial Al Addition on the Structural and Mechanical Properties of TiO2 via Nano-Powder Metallurgy Method - Gatea, Murtadha H; Ali , Alaa Y; Tahatoh, Ayad M; Ali, Mustafa Y (Eximia, 2025)
The addition of nano-Aluminum (Al) to Titanium Oxide (TiO2) using the powder metallurgy method led to significant improvements in the mechanical and structural properties of the resulting composite material. Mechanically, a significant increase in the hardness of the composite material was observed with an increase in the percentage of added Al, reaching a peak value of (80.36 HV) when 20% Al was added. Compressive strength also increased significantly from (33.76 MPa) at 3% Al to 61.29 MPa at 20% Al. Structurally, a decrease in the total porosity of the composite material was observed with an increase in the proportion of Al added, decreasing from 10.91% at 3% Al to (7.17%) at 20% Al. This change in porosity is associated with improved homogeneity and uniformity in the crystal structure of the composite material, which was confirmed by the results of the scanning electron microscope test. It can be said that the addition of Al to TiO2 using the powder metallurgy method has led to clear improvements in the mechanical and structural properties of the composite material, making it more suitable for various engineering applications. XRD analysis confirmed that all composites retained the Monoclinic TiO₂ phase, while the diffraction peaks gradually shifted to higher 2θ values and broadened as the Al content increased—evidence of lattice contraction and reduced crystallite size. These nanostructure changes, revealed by peak broadening and peak‐position shifts, correlate directly with the observed rise in hardness and compressive strength in the Al–TiO₂ composites.